Paternal resistance training induced modifications in the left ventricle proteome independent of offspring diet - Sousa Neto, Ivo Vieira de (2020)
Ancestral obesogenic exposure is able to trigger harmful effects in the offspring left ventricle (LV) which could lead to cardiovascular diseases. However, the impact of the father’s lifestyle on the offspring LV is largely unexplored. The aim of this study was to investigate the effects of 8 weeks of paternal resistance training (RT) on the offspring left ventricle (LV) proteome exposed to control or high-fat (HF) diet. Wistar rats were randomly divided into two groups: sedentary fathers and trained fathers (8 weeks, 3 times per week with weights secured to the animals’ tails). The offspring were obtained by mating with sedentary females. Upon weaning, male offspring were divided into 4 groups (5 animals per group): offspring from sedentary fathers, exposed to control diet (SFO-C); offspring from trained fathers, exposed to control diet (TFO-C); offspring from sedentary fathers, exposed to high-fat diet (SFO-HF); and offspring from trained fathers, exposed to highfat diet (TFO-HF). The LC-MS/MS analysis revealed 537 regulated proteins among groups. Offspring exposure to HF diet caused reduction in the abundance levels of proteins related to cell component organization, metabolic processes, and transport. Proteins related to antioxidant activity, transport, and transcription regulation were increased in TFO-C and TFO-HF as compared with the SFO-C and SFO-HF groups. Paternal RT demonstrated to be an important intervention capable of inducing significant effects on the LV proteome regardless of offspring diet due to the increase of proteins involved into LV homeostasis maintenance. This study contributes to a better understanding of the molecular aspects involved in transgenerational inheritance.